Primate piRNA Cluster Evolution Suggests Limited Relevance of Pseudogenes in piRNA-Mediated Gene Regulation - Gebert, Daniel (Genome Biol Evol, 2019)
PIWI proteins and their guiding Piwi-interacting (pi-) RNAs direct the silencing of target nucleic acids in the animal germline and soma. Although in mammal testes fetal piRNAs are involved in extensive silencing of transposons, pachytene piRNAs have additionally been shown to act in post-transcriptional gene regulation. The bulk of pachytene piRNAs is produced from large genomic loci, named piRNA clusters. Recently, the presence of reversed pseudogenes within piRNA clusters prompted the idea that piRNAs derived from such sequences might direct regulation of their parent genes. Here, we examine primate piRNA clusters and integrated pseudogenes in a comparative approach to gain a deeper understanding about mammalian piRNA cluster evolution and the presumed gene-regulatory role of pseudogene-derived piRNAs. Initially, we provide a broad analysis of the evolutionary relationships of piRNA clusters and their differential activity among six primate species. Subsequently, we show that pseudogenes in reserve orientation relative to piRNA cluster transcription direction generally do not exhibit signs of selection pressure and cause weakly conserved targeting of homologous genes among species, suggesting a lack of functional constraints and thus only a minor significance for gene regulation in most cases. Finally, we report that piRNA-producing loci generally tend to be located in active genomic regions with elevated gene and pseudogene density. Thus, we conclude that the presence of most pseudogenes in piRNA clusters might be regarded as a byproduct of piRNA cluster generation, whereas this does not exclude that some pseudogenes nevertheless play critical roles in individual cases.